HEALTH ISSUES AMONG INDIAN WOMEN’S AND GIRLS: A REVIEW - Awasthi, Radhika (IJRDO-Journal of Applied Science, 2015)
Nutrition plays a significant role in promoting women’s health and fitness. Women’s health is a great issue in developing countries because of numerous hindrances, obstacles and impediments, which force women to ignore their health. Many factors account for the staggering statistics of ill health among women in the developing nations like India but the failure of health systems in the majority of the countries to provide accessible care of adequate quality is a major factor. Unintended pregnancy, Mental health, aging, HIV/AIDs, Noncommunicable diseases, reproductive health etc. are responsible for this.Various government programmes and policies have been framed and some are in the pipeline but the orthodox and obsolete mentality of the people is still a big hurdle and this is the cause that comes in the path of women’ health. This article focuses on the major health issues affecting women’s health.